Integrasi Akal Dan Wahyu Dalam Filsafat Pendididikan Ibnu Sina: Telaah Ontologis Dan Epistemologis - Muhamad Akmal Adiasta; Muhammad Rama Hendring; Faiz Firdaus; Ilham Muhammad Hisyam; Muhamad Parhan (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This article aims to explore the educational thought of Ibn Sina by uncovering its ontological and epistemological foundations. Employing a library research method with a descriptive-analytical approach, this study examines the essential aspects of Ibn Sina’s educational philosophy, starting from his intellectual biography to the conceptual structure of his ideas. The central focus lies in how the concepts of the soul, intellect, and the human relationship with the Divine form the basis of education’s ultimate goal: the perfection of the soul and true happiness (al-sa‘ādah). The study finds that Ibn Sina does not place reason and revelation in opposition, but rather integrates them as the foundation of Islamic education that harmonizes rationality and spirituality. His philosophy offers a compelling alternative to modern educational systems that tend to be overly textual and reductionist, emphasizing instead the importance of shaping complete human beings—intellectually, morally, and existentially. This article is expected to enrich contemporary Islamic educational discourse and serve as a reference for curriculum reform based on the integration of knowledge and values.